Gastric Necrosis After Binge Eating in Bulimia: Recovery From Eating Disorder After Total Gastrectomy - Achamrah, Najate; Grigioni, Sébastien; Coëffier, Moïse; Ainseba, Nadjib; Déchelotte, Pierre (Frontiers in Psychiatry, 2020)
Background Gastric necrosis following acute gastric dilatation is rare but more common in females with eating disorders, such as anorexia nervosa or bulimia, during which patients often alternate restriction and binge eating behaviors. Case Presentation A 37-year old female patient with a history of 15 years of bulimia nervosa was admitted to the emergency department 24 h after binge eating. Abdominal Computed Tomography imaging showed major gastric distension reaching the pelvis and compressing the digestive organs. Total gastrectomy was required because of gastric necrosis. The patient reported significant reduction in bulimic symptoms after gastrectomy. Conclusion We discuss here the possible mechanisms underlying this recovery, including changes in gut-derived factors that could mediate eating behavior changes.